2005
DOI: 10.1111/j.1600-051x.2005.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral malodor‐related parameters in the Chinese general population

Abstract: Tongue coating score, modified sulcus bleeding index and calculus index were factors significantly related to oral malodor in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
144
7
24

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(193 citation statements)
references
References 31 publications
11
144
7
24
Order By: Relevance
“…Population-based studies showed variations in prevalence estimates of halitosis, ranging between 6% and 72%. 2,23,24,25 In comparison with other populations, the prevalence observed in this sample may be considered low. However, this prevalence of approximately 22% may have an important impact, considering that the population studied is composed of dental students.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Population-based studies showed variations in prevalence estimates of halitosis, ranging between 6% and 72%. 2,23,24,25 In comparison with other populations, the prevalence observed in this sample may be considered low. However, this prevalence of approximately 22% may have an important impact, considering that the population studied is composed of dental students.…”
Section: Discussionmentioning
confidence: 98%
“…26,27 Moreover, the hormonal oscillations related to the menstrual cycle, and the changes associated to salivary flow and protein concentration occurring in this period may change VSC concentration and, consequently, the presence of halitosis. 23 Pseudo-halitosis is characterized by the absence of clinical determination of halitosis, but there is a clear complaint about it by the individual. 2,28 This should be contextualized in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las bacterias anaerobias de la cavidad oral degradan sustancias orgánicas denominadas compuestos volátiles de azufre (CVS). En estudios experimentales se ha demostrado que entre el 80% al 90% del mal aliento tiene su origen en los CVS (1)(2)(3)(4)(5). La halitosis también puede ser extraoral (aproximadamente el 4%) por patologías en oído, nariz y garganta, por enfermedades metabólicas, insuficiencia renal o hepática, cambios hormonales, enfermedades bronquiales y/o pulmonares y patologías gástricas (6,7) .…”
Section: Introductionunclassified
“…A despeito de não ter sido mensurado clinicamente, a literatura sustenta que o autorrelato pode ser utilizado como forma de julgar o próprio hálito (Pham, 2013). As causas do hálito ruim podem tanto estar relacionadas ao uso de medicações, distúrbios metabólicos, alteração da composição e diminuição do fluxo salivar devido à DRC (Vesterinen et al, 2007) como à ausência de HO e DP (Liu et al, 2006;Nadanovskyet al, 2007;van den Broek et al, 2007). Mais uma vez, reforça-se a importância da higienização bucal para esses pacientes.…”
Section: Análise Estatísticaunclassified